2010
DOI: 10.1007/s11664-009-1064-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Surface Hardening of Polyurethane Pads During Chemical Mechanical Polishing (CMP)

Abstract: Temperature control to stabilize the microscale contact surface between the pad and wafer, especially to prevent pad surface degradation, plays an important role in chemical mechanical polishing (CMP) processing of sub-50-nm devices. In this work, we investigated the phenomenon of pad surface hardening for various process temperatures and developed an effective method to minimize changes of the mechanical properties of the pad surface using diamond conditioner. The pad hardening characteristics were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This may help the hard pad-particle mixture to induce microscratch on the wafer surface more easily. Recently a few experimental researches have suggested the feasibility of pad-particle mixture or particle-coated pad [9,10]. This simulation work is in good agreement with the experimental works.…”
Section: First Observation On Pad-particle Mixture and Its Effectsupporting
confidence: 82%
“…This may help the hard pad-particle mixture to induce microscratch on the wafer surface more easily. Recently a few experimental researches have suggested the feasibility of pad-particle mixture or particle-coated pad [9,10]. This simulation work is in good agreement with the experimental works.…”
Section: First Observation On Pad-particle Mixture and Its Effectsupporting
confidence: 82%
“…It can be seen that the mode particle size of ceria abrasive without trace metals was 49.6 nm and there was no noticeable change in the particle mode size of the ceria abrasives with FeCl 2 and CrCl 2 up to 100 ppm, nor was there any change in particle number concentration; for the concentrations above 100 ppm however, the number of particles was found to be drastically decreased. A possible cause of this is the reaction of trace metals with hydroxyl groups (-OH) of the base solution, which may result in various salts such as Fe(OH) 3 or Cr(OH) 3 . We attempted to measure the agglomerated ceria abrasive particle number concentration, however we could not measure particle sizes above 300 nm due to limitations of the SMPS used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The material removal rate (MRR) is highly important in CMP to reduce the cost of consumables such as pads, slurries, and conditioners, along with improvisation in the production yield. [3][4][5] For interlayer dielectric (ILD) CMP, the use of ceria-abrasive-based slurries is becoming more prominent because they provide superior CMP performances, including high selectivity, high removal rate, and high planarization efficiency. 6,7 Since ceriaabrasive-based slurries are expensive, their functionality performance needs to be improved via the addition of other materials into the slurries.…”
mentioning
confidence: 99%
“…Borken chatter type of scratches was easily formed when dry slurry paritcles were added but group chatter when pad debris were added. Yang et al [74] measured the pad surface hardening phenomenon based on force-distance (F-D) curves. It was found that the interaction between abrasive particle and polyurethane pad under tribo-mechanical action could change the pad surface hardness.…”
Section: Pad Surface Properties and Pad Debrismentioning
confidence: 99%